The COVID-19 pandemic as a source of negative emotions and misconceptions - a theoretical analysis of the situation - Grajek, Mateusz (Journal of Education, Health and Sport, 2022)
There has been a need to organize the information on COVID-19 that has accumulated in the few months since the emergence of this new disease entity. There are already thousands of scientific publications on COVID-19. On top of that, there are also tens of thousands of press releases, and millions of pieces of information on social media. Being attacked with such an overabundance of information, often contradictory, has confused the public and thus made them susceptible to irrational, false theories about the COVID-19 epidemic. This is a major setback in the fight against the COVID-19 epidemic, which, to be successful, must be conducted in a rational manner. In view of this, the purpose of this article is to gather theoretical knowledge about the impact of the COVID-19 pandemic on the development of negative emotions and frustration in society. The article considers three spheres of consideration: information noise, conspiracy theories, and social risk.